ANALYSIS OF TRAFFIC ACCIDENTS ON HIGHWAY SECTIONS USING THE AEK METHOD: CASE STUDY IN BALURAN NATIONAL PARK - Yohanes Pracoyo Widi Prasetyo (Bulletin of Engineering Science, Technology and Industry, 2023)
Traffic accidents are a significant problem in various areas, including highways that cross National Park areas. This research aims to analyze the level of traffic accidents on roads in Baluran National Park using the Equivalent Accident Number (EAN) method as an evaluation tool. This case study involves collecting data on traffic accidents, traffic characteristics, and related environmental factors. The first step involves collecting traffic accident data from relevant agencies, including accident locations, types of accidents, and victims involved. Risk factors such as speed, traffic volume and road conditions are also identified to support the analysis. The AEK method is then applied to calculate the expected equivalent number of accidents based on traffic characteristics and road parameters. The analysis results show the actual accident rate compared to the calculated AEK. If the AEK is higher, this indicates that the location has a significant risk of accidents. Recommendations for improvement were then put forward, including improving infrastructure, implementing more effective traffic signs, and efforts to increase driver awareness. This research makes an important contribution to understanding and overcoming the challenges of traffic accidents in Baluran National Park. With the AEK approach, policies can be designed to effectively improve traffic safety, while maintaining the environmental sustainability of the National Park.